Health Professionals Addressing Alcohol Use with Pregnant Women in Western Australia: Barriers and Strategies for Communication - Frances, K.; Henley, N.; Payne, J.; D'Antoine, Heather; Bartu, Anne; O'Leary, C.; Elliott, E.; Bower, C. (Informa Healthcare, 2010)
Health professionals have an important role to play in preventing prenatal alcohol exposure. In 2006 qualitative data were collected from 53 health professionals working in primary care in metropolitan and regional Western Australia. Thematic analysis was used to elucidate barriers in addressing prenatal alcohol use and the strategies used to overcome them. Health professionals identified strategies for obtaining alcohol use information from pregnant women but they are not recognizing moderate alcohol intake in pregnant women. Study limitations are noted and the implications of the results are discussed. This research was funded by the Health Promotion Foundation of Western Australia.